The Venus of our anxiety. The first art was visceral. - Cabeca, Paulo (2021)
This work continues the investigation published and aims to demonstrate the phenomenon of artistic creativity in clay as a process of the conscious and subconscious. To this end we will analyze aspects of this Art from its manifestations in the Paleolithic to the present day. Why did the paleolithic man elaborate so many “Venus” female figures in stone, bone and clay? What is the secret of the Paleolithic Venus?